THE IMPACT OF MICROSOMAL PROSTAGLANDIN E SYNTHASE 1 (mPGES1) ON BLOOD PRESSURE IS DETERMINED BY GENETIC BACKGROUND - Facemire, Carie S. (2010)
Prostaglandin (PG) E(2) has multiple actions that may affect blood pressure. It is synthesized from arachidonic acid by the sequential actions of phospholipases, cyclooxygenases, and PGE synthases. While microsomal PGE synthase 1 (mPGES1) is the only genetically-verified PGE synthase, results of previous studies examining the consequences of mPGES1-deficiency on blood pressure (BP) are conflicting. To determine whether genetic background modifies the impact of mPGES1 on BP, we generated mPGES1(−/−) mice on two distinct inbred backgrounds, DBA/1lacJ and 129/SvEv. On the DBA/1 background, baseline BP was similar between wild-type (WT) and mPGES1(−/−) mice. By contrast, on the 129 background, baseline BPs were significantly higher in mPGES1(−/−) animals than WT controls. During angiotensin II infusion, the DBA/1 mPGES1(−/−) and WT mice developed mild hypertension of similar magnitude, while 129-mPGES1(−/−) mice developed more severe hypertension than WT controls. DBA/1 animals developed only minimal albuminuria in response to angiotensin II infusion. By contrast, WT 129 mice had significantly higher levels of albumin excretion than WT DBA/1 and the extent of albuminuria was further augmented in 129 mPGES1(−/−) animals. In WT mice of both strains, the increase in urinary excretion of PGE(2) with angiotensin II was attenuated in mPGES1(−/−) animals. Urinary excretion of thromboxane was unaffected by angiotensin II in the DBA/1 lines but increased more than 4-fold in 129 mPGES1(−/−) mice. These data indicate that genetic background significantly modifies the BP response to mPGES1 deficiency. Exaggerated production of thromboxane may contribute to the robust hypertension and albuminuria in 129 mPGES1-deficient mice.